(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Background: Under the influence of a number of variables, such as the malpractice crisis, shifting societal economics, and shifting environmental regulatory structures, the dental profession is going through a significant transformation. Aim: To review the ethical issues in orthodontics Method of literature search: Between January 2010 and July 2021, a thorough literature search was conducted that covered the notion of smoking rationalization in databases such as Pubmed, Web of Science, ScienceDirect, Ebsco-host, and Google. Nine articles in total were determined to be pertinent, and their conclusions have been examined. Conclusion: Orthodontists are expected to act in the best interests of their patients regardless of their financial situation, and occasionally even at the risk of their own safety, according to the moral traditions and codes of ethics of medicine and dentistry.